Hubungan Pengetahuan Dan Dukungan Keluarga Dengan Sikap Wanita Usia Subur Dalam Pemeriksaan IVA Di Wilayah Kerja Puskesmas Singosari - Sondang Sidabutar; Eka SR Sihombing; Nadya Melina; Nur Anjahaini Azmi Nasution (Jurnal Minfo Polgan, 2025)
Cervical cancer is a serious health problem in Indonesia. Data from 2024 shows that cervical cancer is the second leading cause of death among women in Indonesia, with approximately 36,000 new cases and 21,000 deaths each year. At the Singosari Pematangsiantar Community Health Center, only 25 out of 2,629 women of reproductive age (WRA) underwent IVA screening. This study aims to determine the relationship between knowledge and family support with the attitude of WUS towards IVA screening at the Singosari Community Health Center. This study uses an analytical survey method with a cross-sectional approach. The sample in this study consisted of 96 people, which was taken using non-probability accidental sampling technique. The statistical test used was the chi-square test. The results of the study showed that there was no relationship between knowledge and the attitude of WUS towards IVA screening. The significance value was 0.508 > 0.05. There was a relationship between family support and the attitude of WUS towards IVA screening. The significance value was 0.000 < 0.05. The most influential factor was the attitude of WUS towards IVA screening. It is hoped that the Community Health Center can improve routine counseling for the community and screening through IVA examinations as an effort to detect cervical cancer early.